Pendekatan Fraud Hexagon Untuk Mendeteksi Potensi Kecurangan Laporan Keuangan Pada Perusahaan Properti dan Real Estate di Indonesia - Adhilla Harumningtyas; Shinta Permata Sari (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study aims to analyze the effect of the fraud hexagon elements in detecting fraudulent financial reports which includes six elements, namely stimulus, capability, collusion, opportunity, rationalization, and ego. This research is quantitative research using secondary data. The sample is property and real estate sector companies listed on the Indonesia Stock Exchange (BEI) for the 2021-2023 period. The sampling technique uses a purposive sampling method and there are 54 companies in the sample that meet the criteria. The data analysis technique used in this research is logistic regression analysis using SPSS 25. The results of this research show that the stimulus factor in financial stability and the capability factor in change in director have effect on fraudulent financial reports, while the stimulus factor in financial targets, external pressure, personal financial need; the opportunity factor in the nature of industry, ineffective monitoring; the rationalization factor in change in auditor; the ego factor in the frequent number of CEO's picture; and the collusion factor in cooperation with government project have no effect on fraudulent financial reports.